Infant screening - Shailaja Nikam; Shyamala Dharmaraj (Journal of All India Institute of Speech and Hearing, 1971)
Though a number of studies have been reported elsewhere, none so far have been reported about infant screening in India, and it is not known what would be the personnel requirements and problems associated in carrying out such a programme.